The effects of buckling on the electronic, thermal, and optical features of a GaP nanosheet (JOURNAL OF ADVANCES IN PHYSICS, 2023)
In this paper, an investigation into the electronic, thermal, and optical properties of a nanosheet made of Gallium Phosphide (GaP) via density functional theory (DFT). Our analysis focuses on the impact of buckling processes on these features. The utilization of buckling has been demonstrated to adjust the electronic thermal, and optical characteristics of a GaP nanosheet, including the energy gap, total energy, dielectric function, refractive index, and absorption coefficient. Consequently, the application of buckling in the GaP nanosheet allows for the modulation of its indirect band gap. The feasibility of synthesizing GaP nanosheets experimentally has been proven as these nanosheets exhibit both dynamic and thermal stability. Furthermore, buckling resulted in a broadening and a conspicuous shift towards lower energy in the optical phenomena as the degree of buckling increased. Therefore, it can be concluded that buckling serves as an additional parameter for enhancing the performance of GaP nanosheets in optoelectronic applications.